Notice that x^2 -6x + 8 can be written as (x-4)(x-2)
That's COMMON to the denominator of the other 2 fractions, so that's your COMMON DENOMINATOR
Now, if you multiply EVERYTHING by that common denominator you get
x(x-4) + (x-2) = 2 then simplify and solve
x^2 - 4x + x - 2 = 2
x^2 - 3x - 4 = 0
(x - 4)(x+1) = 0
x = 4
x = -1
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?